2019
DOI: 10.18203/2320-6012.ijrms20193392
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of topical lactobacillus acidophilus and antibiotic in wound repair on the basis of microscopic parameters: a comparative study in rats

Abstract: Background: Wound treatment still a task for medical professionals, according to the time advancement. We need to elaborate further new interventions to cope up this common factor of community. The objective of the study was to assess the anti-inflammatory topical role of Lactobacillus acidophilus with antibiotic in wound repair of rats based on of microscopic parameters. This comparative study was conducted in the Department of Anatomy Al-Tibri Medical Collage and Hospital Isra University Karachi Campus from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Our previous study also related to Probiotics shows how effective it is in initiating angiogenesis and reducing the level of inflammation in rats when it was compared with antibiotics. 21 Steroids aren't recommended for being used to promote wound healing, as the data from our studies also prove that they showed no significant benefit in optimizing angiogenesis. In fact studies indicate that use of systemic steroids has no clinically significant effects on wound healing, furthermore long-term chronic use of steroids can cause an array of complications and can actually prove to impair the wound healing process rather than improve it.…”
Section: Figure-1 Shows the Mean Numbers Of Blood Vessels Among Diffe...mentioning
confidence: 79%
“…Our previous study also related to Probiotics shows how effective it is in initiating angiogenesis and reducing the level of inflammation in rats when it was compared with antibiotics. 21 Steroids aren't recommended for being used to promote wound healing, as the data from our studies also prove that they showed no significant benefit in optimizing angiogenesis. In fact studies indicate that use of systemic steroids has no clinically significant effects on wound healing, furthermore long-term chronic use of steroids can cause an array of complications and can actually prove to impair the wound healing process rather than improve it.…”
Section: Figure-1 Shows the Mean Numbers Of Blood Vessels Among Diffe...mentioning
confidence: 79%